PENGARUH DESAIN KEMASAN PRODUK DAN DAYA TARIK IKLAN TERHADAP KEPUTUSAN PEMBELIAN YANG DIMEDIASI OLEH KESADARAN MEREK PRODUK AIR MINUM CLEO DI KOTA BANDA ACEH - Rizka Pratiwi; Ahmad Nizam (Departemen Manajemen, 2021)
This study aims to find out the Influence of Product Packaging Design and Advertising Attractiveness on Purchasing Decisions Mediated by Cleo Drinking Water Product Brand Awareness in Banda Aceh City. The technique used in the study for sampling is non-probability sampling, with a sample count of 207 respondents. The equipment in the data collection in this study used questionnaires that were distributed directly to the people of Banda Aceh. In this study, researchers used the Structural Equation Modeling (SEM) method as an analysis method to see the influence of all the variables involved. Based on the results of the hypothesis, it states that Product Packaging Design has a significant effect on purchasing decisions. The attractiveness of advertising has a significant effect on purchasing decisions. Product packaging design has a significant effect on brand awareness. The attractiveness of advertising has a significant effect on brand awareness. Brand awareness has a significant effect on purchasing decisions. Brand awareness is able to mediate product packaging design on purchasing decisions. Brand awareness is able to mediate the attractiveness of advertising on purchasing decisions.